2021
DOI: 10.1111/1471-0528.16627
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in pregnancy increases the risk of venous thromboembolism: a nationwide cohort study

Abstract: Objective To investigate if cancer in pregnancy causes a higher risk of venous thromboembolism (VTE) during pregnancy and postpartum compared with pregnant women without cancer. Design A historical prospective cohort study using data from nationwide registries. Setting and population We assessed all pregnancies in Denmark between 1 January 1977 and 31 December 2017. Methods We linked information concerning cancer diagnosis, pregnancy and VTE diagnosis and potential confounders. Event rates of VTE for women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Several patient‐ and delivery‐related risk factors for readmission with VTE were identified, with the most significant being increased maternal age, prolonged hospitalisation and caesarean delivery. The association between these factors and VTE has been consistently demonstrated in previous studies 24,26–29 . Additionally, this study found that low household income and public insurance independently increased the risk of readmission with VTE.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Several patient‐ and delivery‐related risk factors for readmission with VTE were identified, with the most significant being increased maternal age, prolonged hospitalisation and caesarean delivery. The association between these factors and VTE has been consistently demonstrated in previous studies 24,26–29 . Additionally, this study found that low household income and public insurance independently increased the risk of readmission with VTE.…”
Section: Discussionsupporting
confidence: 82%
“…The association between these factors and VTE has been consistently demonstrated in previous studies. 24,[26][27][28][29] Additionally, this study found that low household income and public insurance independently increased the risk of readmission with VTE. This is consistent with the findings of Clapp et al, who reported lower all-cause postpartum readmission rates in women with private insurance and higher income.…”
Section: Main Findingsmentioning
confidence: 53%
“…Treatment strategies have shifted, offering individualised oncological and surgical treatment depending on the cancer type and gestational age whenever possible instead of delaying cancer treatment until after the delivery or induced termination of pregnancy 4–7 . Melanoma, cervical and breast cancer are the most common cancer types presenting during pregnancy 1,8–10 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Melanoma, cervical and breast cancer are the most common cancer types presenting during pregnancy. 1,[8][9][10] Previous studies have shown an increased risk of induced abortion, stillbirth, preterm birth, admission to neonatal intensive care unit (NICU), small-for-gestational age (SGA) and neonatal death in pregnancies complicated by cancer. 5,8,[11][12][13][14][15] In contrast, smaller studies and case reports concerning neonatal and paediatric outcomes after intrauterine exposure to cancer treatment have been reassuring.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated a VTE rate of 75.2 per 10,000 pregnancies with active malignancy compared to 10.7 per 10,000 without malignancy. 27 The present case demonstrated that LMWH VTE prophylaxis can safely be used throughout a pregnancy complicated by active thoracic malignancy and recurrent surgeries without sustaining additional complications related to anticoagulation. but one woman was diagnosed with the disease in pregnancy.…”
Section: Introductionmentioning
confidence: 59%